Impact Evaluation of Raskin Program using Matching Method: Case of IFLS 5 - Sadono, Endiarjati Dewandaru (JEJAK: Jurnal Ekonomi dan Kebijakan, 2018)
Beras untuk Keluarga Miskin (RASKIN) program has been applied since 1998 and has been renamed as Beras Sejahtera (RASTRA) in early 2017, but their effectiveness is still debatable. This study tries to evaluate the impact of RASKIN program on household income. Using data from 3,745 households in Indonesia Family Life Survey (IFLS) 5 that has been estimated using propensity score matching, this study has identified precisely that RASKIN program has a negative and significant effect on household income. This happens because the benefits that reveived by Rumah Tangga Sasaran (RTS) are very small. The small benefit is affected by the amount of rice received, frequency and price that have been paid to get RASKIN is not in accordance with the guidelines. The result of this study is along with previous studies, where the amount and price of rice that distributed through RASKIN program is not exactly correct. Therefore, there must be a change in program format, not just renaming from RASKIN to RASTRA only.